(3GdeZfj aj GdEjKGQ ef ZQjH GdegPH hGdCSeGAs - (3YeGO GdOjf Hf CHj GdHQcGJ Hf HGWjT GdTGaYj GdehUdjs ((3eMeO Hf CHj HcQ Hf CHj GdaJM GdSGhi s)
(3ChdgG (B:s
(3jHOC HGdHGH GdChd ai PcQ GdCSeGA s
(3BNQgG (B:s
(3hef Gddg JYGdi YXje GdLRGA aEf GdEfSGf ZQeg GdNWC hahb cd Pi Yde Ydje hdG Mhd hdG bhI EdG HGddg GdYdi GdYXje Je GdcJGH hGdMeO ddg QH GdYGdejf s
(3GdejcQhajde eXde hZjQ hGVM ai GdJUhjQs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GddZIs